Intervention program in children and adolescents to promote physical fitness, physical activity and nutritional knowledge - Ribeiro, José (2018)
In young people, reduced values of cardio-respiratory fitness (CRF) align themselves with the clustering of cardiovascular risk factors (CVRF). The relationships between volumes, physical activity (PA) intensities and CRF levels on the prevalence and clustering of CVRF have not yet been completely clarified. Assuming that inadequate levels of PA and suitable diets would influence the CRF, the body fat and, therefore, the metabolic profile, it seems prudent to intervene on sedentary behaviors and unhealthy habits to improve cardiovascular health from an early age. Studies involving together the two major determinants of health in these ages: food and exercise are fundamental to the establishment of effective and reasoned health policies. Objective: To assess nutritional knowledge and dietary habits, and PA in a cohort of adolescents before and after an intervention program (IP) of nutritional food education and PA. Methods: PA will be measured by accelerometers and food knowledge through questionnaire (Nutritional Knowledge Questionnaire - NKQ). The IP will be an experimental study based at school and on the internet for promoting healthy behaviors related to PA and healthy nutritional choices, supported by theories of behavioral change. Duration - 9 months involving school and parents community in curricular and extracurricular activities. Results: (1) validation of NKQ (2) explore the associations between CRF, PA and food knowledge; and (3) evaluating the effects of an IP based at school and on the Internet (website), involving the promotion of PA and healthy nutrition behaviors.